2014
DOI: 10.1002/ajim.22376
|View full text |Cite|
|
Sign up to set email alerts
|

Acute symptoms associated with chemical exposures and safe work practices among hospital and campus cleaning workers: A pilot study

Abstract: Study findings suggest a need for additional interventions such as use of less toxic products to reduce health risks among cleaning workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…In EGEA, lifetime exposure to cleaning products was associated with severe and non-allergic asthma 11 . In the four identified workplace-based studies among healthcare workers and cleaners [33][34][35][36] , exposure to cleaning agents or disinfectants was based on self-report, except in one survey in which exposure estimates were enhanced by an evaluation of products compounds 33 . In a French study of hospital workers, a higher risk of asthma was observed among nurses compared to administrative staff, especially for those exposed to quaternary ammonium compounds 33 .…”
Section: Cleaning Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In EGEA, lifetime exposure to cleaning products was associated with severe and non-allergic asthma 11 . In the four identified workplace-based studies among healthcare workers and cleaners [33][34][35][36] , exposure to cleaning agents or disinfectants was based on self-report, except in one survey in which exposure estimates were enhanced by an evaluation of products compounds 33 . In a French study of hospital workers, a higher risk of asthma was observed among nurses compared to administrative staff, especially for those exposed to quaternary ammonium compounds 33 .…”
Section: Cleaning Agentsmentioning
confidence: 99%
“…In a Polish study, almost 60% of the cleaners had work-related allergic symptoms, although skin prick tests and specific IgE antibodies to disinfectants were negative for all subjects 34 . In a U.S. survey, self-reported work-related symptoms were associated with exposure to multi-purpose cleaning products 35 . Finally, results from a two-week panel study among cleaners in Spain, suggested that short-term exposure to irritant cleaning products may exacerbate asthma, especially among non-atopic cleaners 36 .…”
Section: Cleaning Agentsmentioning
confidence: 99%
“…The high frequency of eye exposures (60% of all calls) indicates that safety glasses are not always used, which was supported by the follow-up interviews. Infrequent use of protective equipment has also been noted among hospital cleaners [16]. In a number of cases, protective equipment was available to the participants but nevertheless not used.…”
Section: Discussionmentioning
confidence: 99%
“…Many cleaning products are classified as corrosives and irritants [14]. A pilot study on hospital cleaners noted that symptoms of irritation of the eyes, skin and respiratory tract were frequent; 21.3% experienced such symptoms daily or several times per week and only 43.7% reported no such symptoms in the past 12 months [16]. The focus of cleaning agents' chemical hazards often lies on the long-term effects.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Chemical exposures in the workplace have been linked to adverse health effects such as respiratory (e.g., stuffy nose and cough), ocular (e.g., watery, itchy, or burning eyes), and dermal symptoms (e.g., rash and itchy or burning skin). (11, 12) Some occupational chemical exposures have also been linked to increased risk for cancer (e.g., skin cancer, bladder cancer, and lung cancer). (13) Studies have also shown that occupational outdoor work is associated with increased sunlight exposure, which in turn has led to an increase risk of skin cancer.…”
Section: Introductionmentioning
confidence: 99%